Does competition affect banks’ stability? Evidence from ASEAN economies - Alaeddin, Omar; Abojeib, Moutaz; Ahmed Khattak, Mudeer (Opción, 2019)
This manuscript attempts to investigate the relationship of stability and competition in dual banking economies of ASEAN-5 over the period 2006–2016. We use the Lerner index (LI) as a proxy for banking competition and Z-score is used as a proxy for banking stability as a method. Using the two-step system GMM technique, our results do not indicate any association between competition and stability. In conclusion, one of the benefits that a country can gain form a dual banking system is that it can improve its financial inclusion by attracting customers based on religious needs.